Chapter Variazioni in tema di linguaggio e giustizia amministrativa di fronte al regime - FREDIANI, Emiliano (Studi e saggi, 2021)
The paper focuses on the issue of the impact of the Fascist regime's own language on the activity of the administrative judge. After recalling the problem of the context in which the language of the administrative judge is framed, the investigation highlights some possible "symptoms" of a "sensibility" to be assessed on the level of stylistic and expressive formulas. If, in some cases, this language has been the subject of a particular criticism and attack, in others cases it is possible to highlight how a certain assonance emerges indirectly with the typical speech of the regime. In this perspective, it can be recognized that the linguistic "charm" of the regime, while not affecting the independence of judgment of the administrative judge, had a certain impact on the style of some decisions of the Italian Council of State. An analysis conducted on some paradigmatic cases is able to identify, with regard to a part of the jurisprudence developed after the Thirties, a real "climax" on the linguistic and expressive level.